Nursing Interventions to Improve Blood Glucose Control and Prevent Diabetic Kidney Disease Progression in Type 2 Diabetes Patients - Muhalla, Hafna Ilmy; Nursalam, Nursalam; Bakar, Abu; Sudaryanti, Lestari; Nasir, Abd (Journal of Posthumanism, 2025)
Background - Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion or insulin resistance (ADA, 2023). The most common complication of diabetes is diabetic kidney disease (DKD), which is the leading cause of chronic kidney disease worldwide (KDIGO, 2022). Objective - This study will develop an education and monitoring-based nursing intervention program that integrates technology-based approaches to improve patient compliance with glycemic control. Method - This study uses a pretest-posttest design with a quasi-experimental approach, in which type 2 diabetes patients who experience early signs of diabetic kidney disease will be observed before and after receiving nursing interventions. The variables analyzed in this study were blood sugar control measured through HbA1c levels and kidney disease progression evaluated based on serum creatinine levels and glomerular filtration rate (GFR). Result - Nursing interventions that include patient education, dietary management, regular exercise, and regular blood glucose monitoring are effective in improving blood sugar control in patients with type 2 diabetes and preventing the progression of diabetic kidney disease. In addition to treatment and management of risk factors such as hypertension, a holistic approach involving cooperation between patients and medical personnel is essential to slow down long-term complications. With more advanced technology and more structured monitoring, these interventions are expected to improve patients’ quality of life and reduce the social and economic burden of diabetes. Implication - Appropriate nursing interventions, such as healthy diet education, blood sugar monitoring, and medication support, are essential to control blood sugar levels and prevent diabetic kidney disease in patients with type 2 diabetes. With a coordinated approach, patients can avoid renal complications, improve quality of life, and slow disease progression.